Dutch in 3 months your essential guide to understanding and speaking Dutch - Fenoulhet, Jane (New York, NY DK Publishing, 2022)
"Everything you need to understand and speak Dutch. Free audio app helps you perfect your pronunciation by imitating native speakers. Builds vocabulary through word lists, key phrases, and model sentences. Explains essential grammar. Develops conversation through exercises based on real-life scenarios"--Back cover
"Free audio app."
Includes index
Keywords: Dutch language -- Problems, exercises, etc; Dutch language -- Textbooks for foreign speakers -- English; Dutch language -- Self-instruction; Dutch language; Problems and exercises; Self-instruction; Textbooks -- for English speakers